Stormy days on an open field: Asymmetries in the global economy - Nancy Birdsall (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Openness is not necessarily good for the poor. Reducing trade protection has not brought growth to today's poorest countries, and open capital markets have not been good for the poorest households in emerging market economies. In this paper I present evidence on these two points. First, countries highly dependent on primary exports two decades ago, despite their substantial engagement in trade and a marked decline in their tariff rates in the 1990s, have failed to grow. Second, within high-debt emerging market economies the financial crises of the last decade, whether induced by domestic policy problems or global contagion, have been especially costly for the poor (in welfare terms if not in terms of absolute income losses). I discuss the asymmetries in the global economy that help explain why countries and people cannot always compete on equal terms on the `level playing field' of the global economy. – globalization ; trade ; growth ; income distribution ; development
Keywords: F02; F1; F43; O1; O15; 330; Globalisierung; Außenwirtschaft; Aufstrebende Märkte; Einkommensverteilung; Entwicklung; Finanzmarktkrise